Front Cover: Probing the Entropic Effect in Molecular Noncovalent Interactions between Resin‐Bound Polybrominated Arenes and Small Substrates (ChemPlusChem 9/2018). Issue 9 (15th August 2018) - Yamamoto, Masanori; Obara, Miyuki; Ochi, Keisuke; Yamamoto, Atsushi; Takenaka, Katsuhiko; Tanaka, Tsunehiro; Sato, Kazunori
Abstract : The front cover shows the associative interaction between polybrominated arenes immobilized onto the surface of a resin and small molecules having a diphenylurea backbone. In this system the association and dissociation of the small molecules depends strongly on the particular solvent and on entropy. Understanding and controlling such noncovalent interactions is important for devising sophisticated systems for separation and detection applications. Details are given in the Communication by M. Yamamoto and co‐workers onpage 820 in Issue 9, 2018 (DOI:10.1002/cplu.201800304 ).